2014
DOI: 10.1016/j.phrs.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Depressive behavior in the forced swim test can be induced by TRPV1 receptor activity and is dependent on NMDA receptors

Abstract: Blocking, desensitizing, or knocking out transient receptor potential vanilloid type 1 (TRPV1) receptors decreases immobility in the forced swim test, a measure of depressive behavior. We questioned whether enhancing TRPV1 activity promotes immobility in a fashion that is prevented by antidepressants. To test this we activated heat-sensitive TRPV1 receptors in mice by water that is warmer than body temperature (41°C) or a low dose of resiniferatoxin (RTX). Water at 41°C elicited less immobility than cooler wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 65 publications
(78 reference statements)
2
23
0
Order By: Relevance
“…Activation of TRPV1 by differential ligands or in differential conditions (physiological or pathological) might exert distinct effects on NMDA receptors. This is accordance with the reports that both TRPV1 agonists and antagonists show the antidepressant effects partly through the inhibition of NMDA receptors (Abdelhamid et al, 2014; Amiri et al, 2016; Manna and Umathe, 2012; Sartim et al, 2017). …”
Section: Discussionsupporting
confidence: 93%
“…Activation of TRPV1 by differential ligands or in differential conditions (physiological or pathological) might exert distinct effects on NMDA receptors. This is accordance with the reports that both TRPV1 agonists and antagonists show the antidepressant effects partly through the inhibition of NMDA receptors (Abdelhamid et al, 2014; Amiri et al, 2016; Manna and Umathe, 2012; Sartim et al, 2017). …”
Section: Discussionsupporting
confidence: 93%
“…When the mice are tested again 24 h later, floating times are immediately increased, consistent with the previously reported potentiative effect of conditioning swim on immobility [29]. Fifteen-min conditioning swims on day one are frequently used [26-29] and we previously reported depressive-like behavioral data using that experimental design [24]. …”
Section: Methodssupporting
confidence: 84%
“…AD + AAV EGFP ; Figure d). Besides learning and memory deficits, patients with AD are often accompanied by depression, and laboratory research has shown that TRPV1 activation may affect anxiogenic responses and depression‐related behaviors (Abdelhamid, Kovacs, Nunez, & Larson, ; Kasckow, Mulchahey, & Geracioti, ). We here further found that TRPV1 upregulation by AAV TRPV1 could significantly ameliorate anxiety‐ and depression‐like behaviors in APP23/PS45 mice during the elevated plus maze (Figure a and b), three‐chambered social interaction (Figure c), and force swimming tests (Figure d).…”
Section: Resultsmentioning
confidence: 99%